Proteomic analysis reveals candidate molecules to mediate cortical pathology and identify possible biomarkers in an animal model of multiple sclerosis - Silva, Berenice Anabel (2025)
Introduction: Multiple Sclerosis (MS) is a complex neurodegenerative diseasemarked by recurring inflammatory episodes, demyelination, axonal damage, andsubsequent loss of function. MS presents a wide range of clinical courses, withthe progressive forms leading to irreversible neurological disability. Corticaldemyelinating lesions are central to the pathology of these progressive forms,gaining critical importance in recent decades due to their strong correlation withphysical disability and cognitive decline. Despite this, the underlying mechanismsdriving cortical lesion formation remain poorly understood, and no specifictreatments are currently available. A significant challenge lies in the lack ofanimal models that accurately mirror the key characteristics of these lesions.Methods: We developed a focal cortical animal model that replicates manyfeatures of cortical lesions, including cognitive impairment. This study focuses onconducting proteomic analyses of both the cortical lesions and cerebrospinalfluid (CSF) from these animals, aiming to identify key proteins and biomarkers thatcould be validated in MS patients.Results: Proteomic differences between frontal cortex tissue and CSF wereobserved when comparing experimental animals with controls. Among theidentified proteins, some have been previously described in MS patients andanimal models, while others represent novel discoveries. Notably, we identifiedtwo proteins, S100A8 and orosomucoid-1, that were highly expressed inboth regions.Conclusions: These findings suggest that the prognostic molecules identified inthis model could facilitate the discovery of new biomarkers or key moleculesrelevant to MS, particularly in the cortical lesion that mainly characterized theprogressive forms of the disease.